Extending human healthspan and longevity: a symposium report. Issue 1 (8th September 2021) - DeVito, Loren M.; Barzilai, Nir; Cuervo, Ana Maria; Niedernhofer, Laura J.; Milman, Sofiya; Levine, Morgan; Promislow, Daniel; Ferrucci, Luigi; Kuchel, George A.; Mannick, Joan; Justice, Jamie; Gonzales, Mitzi M.; et al.
Abstract: For many years, it was believed that the aging process was inevitable and that age‐related diseases could not be prevented or reversed. The geroscience hypothesis, however, posits that aging is, in fact, malleable and, by targeting the hallmarks of biological aging, it is indeed possible to alleviate age‐related diseases and dysfunction and extend longevity. This field of geroscience thus aims to prevent the development of multiple disorders with age, thereby extending healthspan, with the reduction of morbidity toward the end of life. Experts in the field have made remarkable advancements in understanding the mechanisms underlying biological aging and identified ways to target aging pathways using both novel agents and repurposed therapies. While geroscience researchers currently face significant barriers in bringing therapies through clinical development, proof‐of‐concept studies, as well as early‐stage clinical trials, are underway to assess the feasibility of drug evaluation and lay a regulatory foundation for future FDA approvals in the future. Abstract : For many years, it was believed that the aging process was inevitable and that age‐related diseases could not be prevented or reversed. The geroscience hypothesis, however, posits that aging is, in fact, malleable and, by targeting the hallmarks of biological aging, it is indeed possible to increase median, if not maximum, longevity.